Distribuição e ocorrência de pinípedes na Ilha Elefante, Shetlands do Sul, Antártica entre 2005 e 2010 a partir de censos aéreos - Trevisan, Mariana Borba (2015)
Pinnipeds are marine mammals of the Carnivora order. Some species were close to the complete extinction due to predatory hunt for their skin and blubber. Conservation measures have been taken to avoid extinction and population monitoring is essential to evaluate how populations are responding along the years. Remote sensing, from satellite images and aerial photographs, allows the monitoring through individual counting without interfering directly in the animals. The main objective of this work is to analyze aspects of the demography and the distribution of pinnipeds in the Elephant Island, located northeast of the Antarctic Peninsula, in the South Shetlands Islands, during the Austral summer (November to March) in the years of 2005 to 2010, using aerial censuses performed around the Elephant Island. The aerial censuses photographs were taken from Squirrel helicopters of the Brazilian Navy flying at a constant speed, 30 to 50 meters height along the island s perimeter. The data were obtained by counting the individuals registered in the photographs. The counting of all censuses summed 27.592 individuals along the years. Due to the fact that it was not possible to cover the totality of the island s perimeter in all censuses, the distribution and occurrence were studied dividing the island into seven sectors along its total perimeter. In general, the species observed more frequently in all sectors were the Southern elephant seals (Mirounga leonina) and Antarctic fur seals (Artocephalus gazella). Even though other seals species such as the Weddell seal (Leptonychotes weddelli), the leopard seal (Hydrurga leptonyx) and the crabeater seal (Lobodon carcinophaga) registered to the Elephant Island exhibited low representativeness in their occupancy, their presence is constant in all censuses. Using the statistical technique Principal Coordinates Analysis, we notice that the occupancy pattern of the Elephant Island by the pinnipeds is related to the substrate present in the different sectors of the island and to the period of the Austral summer sampled. Southern elephant seals settle in sectors of sandy substrate and exhibit the largest occupation during the earlier months of summer (November and December), while Antarctic fur seals preferably settle in rocky substrates and its occupancy is larger during the latest months of summer (January to February). New breeding sites were described in particular for the Antarctic fur seals in so called sectors of Valentin and Piloto Pardo. Preliminary data taken from satellite images of Valentin sector corroborated the aerial photograph data and indicated that the Antarctic fur seals are the predominant species in this region. To our knowledge, this is the first study taken with aerial censuses data in the Elephant Island, and the results presented here have great use for the correct management and conservation politics for the pinnipeds.